1984
DOI: 10.1007/bf00270203
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of carrot somatic embryogenesis by proline and serine

Abstract: Serine and proline, when added in a wide range of concentrations to Daucus carota cultures during pre-growth in the presence of 2,4-D(2,4-dichlorophenoxyacetic acid), extended in time and quantity the mitotic divisions and stimulated significantly the number of embryos regenerated when the hormone subsequently was omitted from the medium. A specific effect of these amino acids on regeneration is suggested, since proline (as hydroxyproline) and serine are the two major constituents of the cell wall glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Somatic embryo induction utilizing 5.13 mM glutamine and GCM was near optimum (Marsolais et al, 1991). Proline is also more effective in promoting embryogenesis in geranium (Marsolais et al, 1991) and a number of other species (Armstrong and Green, 1985;Ronchi et al, 1984;Skokut et al, 1985;Stuart and Strickland, 1984b). For geranium (Marsolais et al, 1991), proline was added as the sole reduced nitrogen source.…”
Section: Discussionmentioning
confidence: 98%
“…Somatic embryo induction utilizing 5.13 mM glutamine and GCM was near optimum (Marsolais et al, 1991). Proline is also more effective in promoting embryogenesis in geranium (Marsolais et al, 1991) and a number of other species (Armstrong and Green, 1985;Ronchi et al, 1984;Skokut et al, 1985;Stuart and Strickland, 1984b). For geranium (Marsolais et al, 1991), proline was added as the sole reduced nitrogen source.…”
Section: Discussionmentioning
confidence: 98%
“…Glutamine was reported being the best by many authors. Recently other amino acids, such as proline and serine were tested and it was shown that they stimulated somatic embryo growth [70]. Sometimes, inorganic nitrogen such as ammonium sulfate can produce growth increments of the embryo of the same magnitude as those observed on embryos growing in a mixture of amino acids [71].…”
Section: Supplementary Elementsmentioning
confidence: 96%
“…Similarly, the role of amino acids in plant regeneration and somatic embryogenesis is known to a considerable extent (Ronchi et al 1984;Chowdhry et al 1993), and small changes in amino acid content evoke various morphogenic responses in an in vitro culture (Dey et al 1998). Muyuan et al (1990) reported increased frequency of differentiation and the percentage of green plant regeneration in Hordeum vulgare callus in a Murashige and Skoog (MS) medium supplemented with amino acids such as alanine, asparagines, and glutamine.…”
Section: Introductionmentioning
confidence: 98%